Gradient residual strain and stress distributions in a high pressure torsion deformed iron disk revealed by high energy X-ray diffraction. (15th March 2018) - Todt, J.; Keckes, J.; Winter, G.; Staron, P.; Hohenwarter, A.
Abstract: High energy X-ray diffraction is used to investigate for the first time the distribution of residual X-ray elastic stresses inside a high pressure torsion (HPT) deformed iron disk with a diameter and thickness of ~ 30 and ~ 8 mm, respectively. In the experiment, a dedicated conical slit system restricts the diffraction gauge volume in three dimensions to ~ 0.45 mm 3, which is then used to scan the bulk sample cross-section in a non-invasive manner. Pronounced residuals stress gradients with maximal tensile stresses of ~ 200 MPa are observed along radial and tangential directions and are correlated to the deformation gradient arising from HPT. Graphical abstract: Image 1